Dispersion management and pulse characterization of graphene-based soliton mode-locked fiber lasers - Abas, Ahmad Fauzi; Lau, Kuen Y.; M. Abdulkawi, Wazie; Alresheedi, Mohammed T.; Muhammad, Farah D.; Mahdi, Mohd Adzir (MDPI, 2022)
This paper presents the generation and characterization of femtosecond pulses utilizing graphene-polymethyl-methacrylate (PMMA) thin-film saturable absorber (SA), which is subjected to different lengths of single-mode fiber (SMF) in an erbium-doped fiber laser cavity. The graphene/PMMA-SA is prepared by using a simple transfer procedure of the thin-film on a fiber ferrule. By increasing the SMF length from 0 to 4 m, the corresponding group velocity dispersion of the entire cavity is estimated to change from −0.033 to −0.121 ps2. Analysis of the pulse performance shows that the pulse width behavior varies from 820 fs to 710 fs against different cavity lengths. Similarly, the pulse repetition rate and the spectral bandwidth can be adjusted from 12.5 to 10.0 MHz, and from 8.2 to 5.6 nm, respectively. A comprehensive discussion on the pulse performance is presented, which can contribute to widening the knowledge on the operation of graphene-based soliton mode-locked erbium-doped fiber lasers based on dispersion management by controlling the cavity length.